Procalcitonin and quantitative C-reactive protein role in the early diagnosis of sepsis in patients with febrile neutropenia - Meidani, Mohsen; Khorvash, Farzin; Abolghasemi, Hojat; Jamali, Bahareh (South Asian Journal of Cancer, 2013)
Background: Neutropenia with fever is a common syndrome in patients with hematologic malignancies who have a high risk of infectious diseases. As early diagnosis of infection in such patients is really important, the aim of this study was to investigate the sensitivity and specificity of procalcitonin (PCT) and C-reactive protein (CRP) in the diagnosis of sepsis in febrile neutropenic patients in a referral malignant care center of Isfahan in 2010-2011. Materials and Methods: In this analytical cross-sectional study, all the febrile neutropenic patients who were admitted in the referral malignant care center in 2010-2011 were evaluated. The data from every individual, including sex, age, admission time, and duration of fever before taking antibiotics were collected. Sixty-four subjects were involved in the study. Blood samples of the subjects were obtained and the levels of PCT, CRP, Absolute neutrophil count (ANC), and white blood cell count were measured, and blood cultures were obtained. According to the test results, the 64 subjects were divided into two groups including patients with sepsis and without sepsis. Results: Mean value of PCT in the sepsis group was 28.65 ± 2.68 and in the non-sepsis group was 2.48 ± 0.66, with a P value of 0.000. In case of CRP, the sepsis group had a mean of 159.48 ± 9.73 and the non-sepsis group had a mean of 126.17 ± 10.63 (P = 0.015). Sensitivity and specificity were analyzed by using receiver operating characteristic (ROC) curve and were found to be 92.5% and 97.3%, respectively, for PCT and 70.5% and 42.1%, respectively, for CRP. Conclusion: PCT can be considered as a predictive factor and a diagnostic marker for the diagnosis of sepsis in febrile neutropenic patients.
Keywords: C-reactive protein; fever; neutropenia; procalcitonin